2021
DOI: 10.1038/s41419-021-03584-0
|View full text |Cite
|
Sign up to set email alerts
|

hPER3 promotes adipogenesis via hHSP90AA1-mediated inhibition of Notch1 pathway

Abstract: The period circadian regulator 3 (PER3) has been reported to play a negative role in human immortalized bone marrow-derived Scp-1 cells (iBMSCs) and patient adipose-derived stromal cells (PASCs) or a negative/positive role in mice adipogenesis. However, human PER3 (hPER3) was identified as a positive regulator of human adipose tissue-derived stromal cells (hADSCs) adipogenesis in this study. Silencing or overexpression of hPER3 in hADSCs inhibited and promoted adipogenesis in vitro. In vivo, the overexpression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…The EthD-III staining experiments found that EthD-IIIpositive cells existed in the dentate gyrus and pyramidal cells in hippocampal and cortex tissues. The pyroptotic cells looked like cabbage or fried egg, with the nucleus located in the center [25]. The results showed that the level of pyroptosis was elevated in both the hippocampal and cortex tissues of septic hsf1 -/and hsf1 +/+ CLP models contrasted to the sham control, respectively.…”
Section: Pyroptosis Is Elevated In Brainmentioning
confidence: 88%
See 1 more Smart Citation
“…The EthD-III staining experiments found that EthD-IIIpositive cells existed in the dentate gyrus and pyramidal cells in hippocampal and cortex tissues. The pyroptotic cells looked like cabbage or fried egg, with the nucleus located in the center [25]. The results showed that the level of pyroptosis was elevated in both the hippocampal and cortex tissues of septic hsf1 -/and hsf1 +/+ CLP models contrasted to the sham control, respectively.…”
Section: Pyroptosis Is Elevated In Brainmentioning
confidence: 88%
“…The induction of HSPs responsible for maturation, antioxidative protection, adiposis, etc., can be significantly affected by harmful stress such as reactive oxygen species (ROS) and inflammation [18][19][20]. Interacting with other signaling pathways, HSPs can produce a collective response against harmful stress like sepsis [21][22][23][24][25]. HSPs are evolutionarily conserved and involved in the cellular protective mechanism of heat shock response (HSR) to maintain protein homeostasis in almost all eukaryotic cells.…”
Section: Introductionmentioning
confidence: 99%
“…Other genes may also be involved in different aspects of the anti-obesity regulatory process. For instance, the PPARG can regulate systemic insulin resistance, PPARG dysregulation will cause obesity, and HSP90AA1 can inhibit the reduction of adipogenesis through the in vivo pathway to trigger the anti-obesity effect [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, circadian rhythm controls the majority of genes activity that involves various diseases including bone diseases, arthritis, aging, and metabolic diseases 32,37,38 . As one of the circadian controlled genes, NOTCH1 can be regulated by PER3 during adipogenesis 39 . H Angharad Watson found the L-selectin (CD62L) can increase the T cells to eliminate cancer cells 40 .…”
Section: Discussionmentioning
confidence: 99%